Rethinking Turkey's position in the Middle Eastern regional security complex: from insulator to regional leader? - Luenam, Jitlaeka (AUC Knowledge Fountain, 2014)
The outlier states that are at the peripheral of other regions normally play a conspicuous role in the system. This is because they are hardly identified as part of any region. In Buzan and Waever’s Regional Security Complex Theory (RSCT), these states are called “insulator”. Insulator does not locate in the regional security complex but rather sits at the margin between two or more regional security complexes. Furthermore, insulators also play a passive role: either by inhibiting the zone of relative indifference or absorbing the energy of RSCs’ periphery. Turkey is acknowledged by Buzan and Waever as an insulator because it exists at the peripheral of three RSCs—the EU, the Middle East, and the ex-Soviet. Despite its active participation in the surrounding RSCs, it remains an insulator because it is not able to bring different regional security complexes together to form its own strategic arena or to clearly present itself as a pole in any regional security complex. The RSCT may have been accurate in portraying Turkey’s regional position in the last decades but it is unclear whether this positioning can be imposed on Turkey under the rule of the AKP. This is because this positioning of Turkey as an insulator was done by Buzan and Waever back in 2003 when they introduced the RSCT as a grand theory in their book, Regions and Powers. Since 2003 Turkey has been through various changes and there have been many of the foreign policy initiatives of the AKP government. Therefore, the role of Turkey as an insulator should be reconsidered. This research proposes to explore whether Turkey under the rule of the AKP does not fit anymore in to the category of insulator state within the RSCT because it has become a pole in the Middle Eastern Regional Security Complex, by analyzing changes of Turkish foreign policy under the rule of the AKP. The answer to the question will be done from a comparative analysis by comparing Turkish foreign policy in two main periods: the pre-AKP era and the AKP era. The comparison will be focused on three main themes, Israeli-Palestinian issue, nuclear policy and the debates on Islamic democracy to assess the interconnectedness of Turkey and the Middle East in the societal and the political sectors. In order to see if the AKP has been the main factor that led to these changes, the research will then analyze dynamics that led to changes of Turkish foreign policy under the rule of the AKP by looking into two different levels: systemic and domestic. By doing so, the research can differentiate between changes in Turkish foreign policy that are primarily reactive and/or determined by changes in the international and regional structure and those that are related explicitly to the AKP policies.